Hallazgo de un tercer ejemplar de Myxine pequenoi (Ciclostomi, Myxinidae), con comentarios sobre los ciclóstomos marinos de Aysén, Chile - Pequeño, Germán; Figueroa-Muñoz, Guillermo (Revista de Biología Marina y Oceanografía, 2021)
The capture of a specimen of Myxine pequenoi until 550 km south of the previously described distribution, specifically from Seno Magdalena, Puerto Cisnes, Aysén, is communicated. The extension of the geographic distribution of M. pequenoi was analyzed, in a wider spectrum about the marine cyclostomes, in the Chilean fjord’s region.